Digital Storytelling-Based English Learning as an Effort to Preserve Local Literary Works in the Oemah Baca Warna Warni Community - Sulistyawati, Anin Eka; Yuvita, Yuvita; Rofiudin, Rofiudin (ASEAN Journal of Empowering Community, 2025)
This community service program was implemented to address low English literacy levels and the gradual decline of storytelling traditions in Pegirikan Village, Tegal Regency. The program builds upon previous initiatives that aimed to increase children’s reading interest and strengthen the local literacy community. The implementation procedures included partner needs mapping, multimodal literacy training, digital content creation workshops, participant development observation, and documentation of learning outcomes. The participants involved in this program consisted of community volunteers, university students as facilitators, and children as the main target group. Observations were conducted by examining participants’ engagement during training sessions, their ability to use digital applications, and children’s responses during English learning activities. The indicators of success included increased active participation, improved technical skills, and positive changes in learning motivation. The program outcomes demonstrated a noticeable increase in participant engagement, particularly in storyboard design skills and the production of digital fairy tale videos. Children also showed improvement in their mastery of simple English vocabulary, accompanied by positive responses toward storytelling activities based on local content. The most significant impact of the program was observed among community volunteers, who were able to independently develop digital learning products after receiving mentoring. These findings support multimodal literacy theory, which emphasizes the integration of text, visual, and audio elements to enhance learning effectiveness. In conclusion, the development of folklore-based digital fairy tales proved effective in improving English literacy while simultaneously preserving local culture. In addition, the program strengthened the community’s capacity to independently utilize technology. Therefore, it is recommended that future activities focus on expanding content production and developing promotional strategies to ensure program sustainability.